Hubungan antara Prokrastinasi Akademik dengan Prestasi Belajar Siswa Kelas IV SD Gugus III - St Jauhar; Nur Mutmainnah; Awaluddin Muin (Universtas Negeri Makassar, 2022)
The problem in this research is the emergence of academic procrastination among students, thus affecting students learning achievement in school. This study is a quantitative study with a correlation design that aims to determine the relationship between academic procrastination and students learning achievement of IV grade SD Cluster III. The results showed that there was a significant negative relationship between academic procrastination and students learning achievement in IV grade SD Cluster III with a comparison tcount value of -0.222 was greater (>) ttable value of 0.156, so H0 was rejected and H1 was accepted. Based on the results of the data analysis, it can be concluded that academic procrastination has an unfavorable impact on student learning achievement. So, the higher the level of student academic procrastination, the lower the student's learning achievement. Thus, it can be seen the impact resulting from this study that academic procrastination can reduce student learning achievement.